Skrining Fitokimia Dari Infusa Dan Ekstrak Etanol 70% Daun Cincau Hijau(Cyclea barbata Miers) - Siti Nur Oktavia; Endang Wahyuningsih; Sholikhah Deti Andasari; Normaidah (CERATA Jurnal Ilmu Farmasi, 2020)
Green grass jelly leaf (Cyclea barbata Miers) is a plant that has many benefits with the content of green grass jelly leaves (Cyclea barbata Miers) which are carbohydrates, fats, proteins and other compounds such as polyphenols, flavonoids and minerals such as calcium, phosphorus, vitamin A, and vitamin B. This study aims to determine the comparison of the results of the phytochemical screening of infusion and green grass jelly leaf extract (Cyclea barbata Miers). This research is a type of experimental research conducted at the Laboratory of Pharmaceutical Analysis STIKES Muhammadiyah Klaten. The research stages included sample preparation, extraction process, and phytochemical screening. The data analysis of this research is in the form of qualitative, the data is presented in tabular form and then the results are described. The results of phytochemical screening on green grass jelly leaves showed that the maceration and infusion processes of green grass jelly leaves contain flavonoids, alkaloids, saponins, and tannins. The difference is in the color change that occurs from the results of determining the flavonoid compounds, the results show that the color of the maceration extract is brownish yellow, while the color in the infusion is yellow. The conclusion of this study shows that green grass jelly leaf extract contains flavonoids, alkaloids, saponins, and tannins.